Intelligence and Mental Imagery in Intellectual Disability - Santo F. Di Nuovo (Mediterranean Journal of Clinical Psychology, 2018)
After a presentation of the main model for conceptualizing and measuring intelligence, the importance of Mental Imagery in determining the cognitive performances in Intellectual Disability is underlined.